EFFECT OF ARSENIC ON DRY WEIGHT AND RELATIVE CHLOROPHYLL CONTENT IN GREENINGMAIZE AND SUNFLOWER TISSUES - Szilvia Várallyay (Journal of Microbiology, Biotechnology and Food Sciences, 2015)
Arsenic is one of the most toxic elements that can be found in the environment. Excessive uptake of arsenic may cause physiological changes in plants. The aim of the study was to investigate the effect of different arsenic treatments on relative chlorophyll content and dry weight of shoot and root of maize and sunflower in the early phases of plant development. Seedlings were grown in climatic room in nutrient solution under strictly regulated environmental conditions. The plants were exposed to 3, 10 and 30 mg kg-1arsenic, whereas there was no arsenic treatment on the control plants. We applied arsenic in the form of arsenite (NaAsO2) and arsenate (KH2AsO4), respectively. After 14 days of arsenic treatments, changes in relative chlorophyll content and dry weight of maize shoots and roots were recorded. In the case of sunflower these physiological parameters were measured after 21 day. The applied arsenic decreased the relative chlorophyll content of maize and sunflower leaves, especially at concentration of30 mg kg-1. The increasing amount of As treatment were resulted the lower weight of the experimental plants, which was more considerable in the case of the roots. The results indicate that the sunflower plants is more sensitive to arsenic toxicity than maize plants and all data demonstrate that the As(III) is more toxic to these crop plants than the As(V).